2022
DOI: 10.1002/anie.202214213
|View full text |Cite
|
Sign up to set email alerts
|

Modular and Fast Synthesis of Versatile Secondary α,α‐Dialkyl Boronates via Deoxygenative Alkylboration of Aldehydes

Abstract: Secondary α,α-dialkyl boronates are widely used due to their great versatility. Herein we report an unprecedented deoxygenative alkylboration of aldehydes, a facile method to access this type of products. A sequence of difunctionalization can be obtained smoothly from the readily available aldehydes in only two steps. This difunctionalization of aldehydes rather than conventional alkenes also opens new possibilities within the field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 107 publications
0
17
0
Order By: Relevance
“…Based on these mechanistic results and previous works, , a proposed catalytic cycle is listed in Scheme . The oxidative addition of α-chloroboronate with ( L1 )­Ni­(I) I generated the Ni­(III) intermediate II , which can proceed to ring-opened or -closed processes with radical-clock substrates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these mechanistic results and previous works, , a proposed catalytic cycle is listed in Scheme . The oxidative addition of α-chloroboronate with ( L1 )­Ni­(I) I generated the Ni­(III) intermediate II , which can proceed to ring-opened or -closed processes with radical-clock substrates.…”
mentioning
confidence: 99%
“…The halo-exchanged and dehaloprotonation compounds were detected as the main products in these two reactions. These experiments likely exclude the oxidative addition with a zerovalent nickel catalyst; instead, it could occur with Ni­(I) species, which is in accordance with our previous C­(sp 3 )–C­(sp 3 ) coupling . Furthermore, the luminescence quenching experiments with different substrates indicated that HEH was mainly responsible for reductive quenching of the active state of the photocatalyst as previously (see Supporting Information).…”
mentioning
confidence: 99%
“…A central research program of our laboratory has been the development of novel Mo-catalyzed deoxygenative functionalization reactions of carbonyl compounds, thus circumventing the use of hazardous diazo compounds. , A major challenge of this goal is to both cleave the strong CO double bonds ,, and control the selectivities including regio-, chemo-, and stereoselectivities. Enabled by the (chiral) low-valent molybdenum catalysts, an intramolecular deoxygenative C–H bond functionalization, an intramolecular (asymmetric) deoxygenative cyclopropanation, , an intramolecular deoxygenative C–N bond formation, an intermolecular deoxygenative formal N–H insertion/carbonyl–carbonyl olefination cascade process, and homodimerization of aldehydes as well as intramolecular deoxygenative olefination of dicarbonyl compounds have been respectively developed by Asako, Takai, Ilies et al, and our laboratory.…”
mentioning
confidence: 99%
“…10 To this end, very recently, we have developed a modular and facile route to afford the target products by utilization of commercially available or easily prepared aldehydes as precursors via deoxygenative difunctionalization of carbonyls (DODC) strategy. 11 The mild conditions (visible light, room temperature, no strong base), the readily available reagents, and the versatility of the products, enable a very wide scope and offer great potential in organic synthesis (Scheme 1 B).…”
mentioning
confidence: 99%